Hubungan Antara Penerapan Program Sanitasi Total Berbasis Masyarakat (STBM) dengan Kejadian Diare di Tingkat Rumah Tangga (RT) Studi di Wilayah Kerja Puskesmas Kebasen Kecamatan Kebasen Kabupaten Banyumas - Paramastri, Nerpadita; Nurjazuli, Nurjazuli; Setiani, Onny (Jurnal Riset Kesehatan Masyarakat, 2021)
The incidence of diarrhea in the Kebasen Subdistrict is still high. The implementation of the Community Led Total Sanitation (CLTS) program has not run optimally in the Kebasen Subdistrict area judging by the unfulfilled standard criteria and requirements of the 5 pillars of CLTS.This research focused on observasional analytical study with cross sectional approach. The population in this study was all households in the working area of Kebasen Health Center with a total of 100 households. The sampling technique using proportional random sampling.Data analysis using chi square test.The results showed that 27% of households defecate carelessly, 81% do not apply handwashing with soap, 47% do not manage food and drink safely, 91% do not safely safeguard waste, and 80% do not safely safeguard liquid waste. There is a relationship between the implementation of CLTS in stop open defecation free aspect (p=0,000), handwashingwith soap aspect (p=0.021), household drinking water and food management aspect (p=0.000), and household waste watermanagement aspect (p=0.014) with the occurrence of diarrhea in the working area of Kebasen Health Center. There is no relationship between the implementation of CLTSin household waste management aspect (p=0.471) with the occurrence of diarrhea in the working area of Kebasen Health Center. The incidence of diarrhea in the working area of Kebasen Health Center is influenced by the habit of people who behave defecation carelessly, do not washing hands with soap, unsafe food and beverage management, and the absence of liquid waste security.